Pull straighten and push technique: A simple solution for guidewire realignment to facilitate stent and device delivery in coronary angioplasty - Kachery, Byju; Ephrem, Biju; Gopalakrishnan, Sreeram (Indian Journal of Case Reports, 2020)
Coronary guidewire bias prevents easy passage of interventional devices such as stents and balloons during percutaneous coronary intervention (PCI). Realigning guidewire into the central part of the lumen, away from the coronary wall helps the tracking devicesin situations with significant guidewire bias. There are several available techniques to facilitate stent delivery in tortuous vessel; however, these techniques have their own limitations and can be expensive and time-consuming. A new maneuver for easy passageof stents and balloons in these situations by guidewire realignment is described in this report. This maneuver namely “pull straighten and push technique” demonstrated an easy procedure to successfully execute stents or devices deployment in challenging PCIs.